2014
DOI: 10.1128/aac.02932-14
|View full text |Cite
|
Sign up to set email alerts
|

Antistaphylococcal Activity of Oritavancin and Its Synergistic Effect in Combination with Other Antimicrobial Agents

Abstract: Oritavancin exhibited in vitro activity against 169 strains of vancomycin-susceptible, methicillin-resistant Staphylococcus aureus (MRSA) with MICs ranging from 0.03 to 1 g/ml and against vancomycin-intermediate MRSA (VISA; n ‫؍‬ 29), heterogeneous vancomycin-intermediate MRSA (hVISA; n ‫؍‬ 5), and vancomycin-resistant MRSA (n ‫؍‬ 5) strains, with MICs ranging from 0.12 to 4 g/ml. For 10 MRSA isolates comprising 5 VISA and 5 hVISA strains, synergy between oritavancin and gentamicin, linezolid, or rifampin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…In the case of standard MRSA, all isolates in the present study were inhibited by ORI at a concentration not exceeding 0.063 g/ml, a value that corresponds to the published MIC 90 from surveillance of over 9,000 S. aureus isolates (6). With regard to strains of the more resistant phenotypes, such as hVISA, VISA, and DNS MRSA, the ORI MIC values obtained in our study were lower than those reported previously, where the ORI MICs against hVISA, VISA, and DNS MRSA isolates ranged up to 2 g/ml (6,18). In our study, 12 of 15 (80%) hVISA, VISA, or DNS MRSA isolates were susceptible to ORI, with MIC values being 0.25 g/ml for only three VISA isolates.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In the case of standard MRSA, all isolates in the present study were inhibited by ORI at a concentration not exceeding 0.063 g/ml, a value that corresponds to the published MIC 90 from surveillance of over 9,000 S. aureus isolates (6). With regard to strains of the more resistant phenotypes, such as hVISA, VISA, and DNS MRSA, the ORI MIC values obtained in our study were lower than those reported previously, where the ORI MICs against hVISA, VISA, and DNS MRSA isolates ranged up to 2 g/ml (6,18). In our study, 12 of 15 (80%) hVISA, VISA, or DNS MRSA isolates were susceptible to ORI, with MIC values being 0.25 g/ml for only three VISA isolates.…”
Section: Discussioncontrasting
confidence: 54%
“…However, only CPT in combination with ORI was able to demonstrate synergy against standard MRSA and hVISA strains as well. Previously, a study evaluated the activity of ORI in combination with gentamicin, rifampin, and linezolid against MRSA, and the authors demonstrated synergistic effects between ORI and each of these agents (18). However, ours is the first study to evaluate ORI in combination with beta-lactam antibiotics.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Synergy has been demonstrated in vitro between oritavancin and aminoglycosides, b-lactams, linezolid, or rifampin against MRSA or enterococci [90][91][92][93] as well as between telavancin and b-lactams, aminoglycosides, or rifampin against MRSA [94,95], or dalbavancin and oxacillin against MRSA [96].…”
Section: In Vitro Pharmacodynamicsmentioning
confidence: 99%
“…Additional in vitro investigations support potential future studies regarding use against VRE infections (20), methicillin-resistant S. aureus (MRSA) infections with the novel mecC gene mechanism or infections emerging in the community setting (21,22), some S. aureus strains with elevated vancomycin MIC values or heteroresistant variations (23,24), and uncommonly isolated Gram-positive species (25). Furthermore, favorable in vitro drug combination (synergy) results have been reported for oritavancin testing against staphylococci (26). With this favorable microbiological, PK/PD, and clinical trial background, oritavancin provides a valuable addition to our antimicrobial armamentarium to treat infections caused by resistant Gram-positive cocci.…”
mentioning
confidence: 99%